Working conditions of healthcare personnel facing the pandemic in Latin America: an integrative review - Saltos Llerena, Irma Jeannette (Universidad de Sonora, 2022)
Introduction: Healthcare personnel are the most exposed to infection while they care for the patients with COVID-19. Knowing the studies carried out with respect to the working conditions of the healthcare personnel in Latin America, will enable the detection of the necessary and less treated lines of research, deficiencies and to trace the main lines of work for their solution. Objective: To determine, by means of an integrative literature review, the working conditions of healthcare personnel who faced the pandemic in the region, its consequences and the behavior of the responsible stakeholders. Methodology: Integrative review applying the Ganong method, by means of pairs of key words. The documents were classified by categories of study such as working conditions, health consequences of inadequate conditions and the role of the stakeholders responsible for ensuring satisfactory working conditions. Twelve original and review articles were selected, which provided quantitative data from research carried out with healthcare personnel in the region. Duplicate publications, reflections, letters and other articles that did not provide elements of substantiation were excluded. Results: Results show high percentages of deficit of personal protection equipment, extreme working conditions that caused infection, lack of biosecurity measures, insufficient training, labor and social security rights were violated by the stakeholders responsible for guaranteeing them. Conclusions: Working conditions were inadequate and unsafe. Healthcare personnel were affected physically, psychologically and economically, thus, demanding governments and health institutions to play a role in their solution.